INNOVATIONS IN THE CREATION OF ECOLOGICAL FOOD PACKAGING - Піддубний, Володимир; Тарасюк, Галина; Чагайда, Андрій; Радченко, Юрій (SWorldJournal, 2024)
The main goal of food packaging, from the point of view of sustainable development, is to reduce product losses starting from production and along the supply chain. The creation of ecological packaging is becoming more and more urgent due to the worsening